«16-19-րդ դարերի հայ ազգային-ազատագրական շարժումները» թեմայի դասավանդումը դպրոցում - Առստամյան, Ա. Բ.
В данной статье обсуждаются методы методы преподавания темы “Армянские освободительные движения в 16-19 вв.”. В статье выражается мысль о том, что данные темы могут способствовать национальному самосознанию учеников․ This article discusses the teaching methods and characteristics of Armenian liberation movements in 16-19th centuries, at school. Here the idea that these topics can be best contribute to the education of students in Armenian spirit is discussed․
Keywords: Պատմություն; Դասավանդման մեթոդներ